2017
DOI: 10.5433/1679-0359.2017v38n3p1323
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of animal performance, feed intake, and economic losses in sheep experimentally infected with Trypanosoma vivax

Abstract: Trypanosoma vivax is a protozoan originating from the African continent, which, although it has not yet been able to complete its biological cycle in South America, due to the absence of the tsetse fly, can still cause death in ruminants. The objective of this study was to verify the effects of T. vivax on the measurements and indices in sheep that characterize animal performance, as well as on economic losses in meat animals. Twenty intact adult male sheep were used for this study, all of approximately the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
2
0
0
Order By: Relevance
“…There was no significant (P > 0.05) change in mean group proportional body weight gains of all the experimental animals from weeks 1 to 10 PI. This result agrees with the findings of Akpa et al (21), who reported no loss of weight in bovine trypanosomosis, but it differs from those of some researchers who reported cases of weight loss in trypanosomosis (22). Significant (P < 0.05) increase in proportional body weight gain was recorded from week 11 to the end of the study in group 5 (DA + vitamin A 3 weeks PI) when compared with all the other experimental groups.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There was no significant (P > 0.05) change in mean group proportional body weight gains of all the experimental animals from weeks 1 to 10 PI. This result agrees with the findings of Akpa et al (21), who reported no loss of weight in bovine trypanosomosis, but it differs from those of some researchers who reported cases of weight loss in trypanosomosis (22). Significant (P < 0.05) increase in proportional body weight gain was recorded from week 11 to the end of the study in group 5 (DA + vitamin A 3 weeks PI) when compared with all the other experimental groups.…”
Section: Discussionsupporting
confidence: 88%
“…Clinical signs of pale mucous membranes, anorexia, facial edema, and enlargement of prefemoral and prescapular lymph nodes observed are characteristic of trypanosomosis in animals (22,25). Muscular spasms, circling, and torticollis observed in some sheep before treatment agrees with the findings of Desquesnes et al (30), who reported nervous signs in T. evansi infections of sheep and goats.…”
Section: Discussionsupporting
confidence: 87%